2014
DOI: 10.1136/thoraxjnl-2014-205513
|View full text |Cite
|
Sign up to set email alerts
|

Investigating and managing suspected pulmonary embolism in an outpatient setting: the Leicester experience

Abstract: Having established an ambulatory service for patients with suspected and proven PE, we reviewed our outcomes. All patients referred from June 2010 to May 2012 were analysed. Of 971 patients referred, 905 underwent complete assessment (66 admitted as ineligible). 754 (77.7%) patients were discharged and required no follow-up. 96 (10.6%) patients had PE confirmed of whom 70 (72.9%) were managed as outpatients. 14 (1.6%) patients have died since attending the clinic; no death was related to PE. This audit shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…No mortality occurred in these patients during a follow-up of 90 days [14]. It may be concluded that mortality decreases when the number of restrictions for outpatient treatment are increased.…”
Section: Discussionmentioning
confidence: 83%
“…No mortality occurred in these patients during a follow-up of 90 days [14]. It may be concluded that mortality decreases when the number of restrictions for outpatient treatment are increased.…”
Section: Discussionmentioning
confidence: 83%
“…The safety and efficacy of such an approach is further supported by a large randomized controlled trial as well as a recent small observational study . Indeed, outpatient management of low‐risk PE patients is quite common in both Europe and Canada …”
Section: Rationale For Outpatient Management Of Low‐risk Pe Patients mentioning
confidence: 91%
“…Of the 971 patients referred, 871 were treated entirely as OPs (89.7%) 12 . The authors report previous pilot work suggesting this cohort of patients previously had a mean LOS of 1.59 days, resulting in 692 saved bed-days per year.…”
Section: Outcomes Of Op Care For Low-risk Pementioning
confidence: 98%
“…Vali et al 12 used a modified version of the PESI in combination with a series of clinical exclusion criteria (pulse <110 bpm, SBP >100 mm Hg, oxygen saturations >92% on air, respiratory rate <30 bpm, no syncope, normal troponin, no large central clot or right heart strain on CTPA, no compliance or follow-up issues, low risk of bleeding, did not require admission for other comorbid conditions) to identify patients with suspected PE who were suitable for OP management. Using these criteria they managed 72.9% of patients with confirmed PE as OPs with PE-specific mortality of 0%.…”
Section: Inclusion and Exclusion Criteria For Op Management Or Early mentioning
confidence: 99%
See 1 more Smart Citation